2014
DOI: 10.2527/jas.2013-6551
|View full text |Cite
|
Sign up to set email alerts
|

The effects of porcine intestinal mucosa protein sources on nursery pig growth performance1

Abstract: Three studies were conducted to compare the effects of 4 different porcine intestinal mucosa products (PEP2, PEP2+, Peptone 50, and PEP-NS; TechMix Inc., Stewart, MN) with select menhaden fish meal (SMFM) on nursery pig performance. These intestine-derived mucosal ingredients are byproducts of heparin production, with a similar amount of mucosal protein, but differ based on the carriers with which they are co-dried. Enzymatically processed vegetable protein is the carrier for PEP2 whereas PEP2+ is co-dried wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 13 publications
2
13
0
Order By: Relevance
“…Consumption of feed containing the hydrolysates, PDP or SDP-PDP, enhanced the productive performance of piglets compared to their corresponding control group, and these groups were equivalent to the SDP group. This result is in accordance with other authors who also obtained similar growth performance by feeding PDP and SDP in early-weaned piglets [51]. Some research data have shown improved growth performance, feed intake and e ciency of animals fed PDP compared to other highquality protein sources like sh meal [46].…”
Section: Discussionsupporting
confidence: 91%
“…Consumption of feed containing the hydrolysates, PDP or SDP-PDP, enhanced the productive performance of piglets compared to their corresponding control group, and these groups were equivalent to the SDP group. This result is in accordance with other authors who also obtained similar growth performance by feeding PDP and SDP in early-weaned piglets [51]. Some research data have shown improved growth performance, feed intake and e ciency of animals fed PDP compared to other highquality protein sources like sh meal [46].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, pigs fed S50 and HP300, two sources of ESBM, had similar growth performance to fish meal, which was in agreement with Jeong and Kim () who found no differences on growth performance, nutrient digestibility, and fecal microflora in weaned pigs when HP300 replaced half of the fish meal in diets. In addition, no differences appeared in performance of pigs fed either CDCP, P50, or fish meal diets, which may be attributed to low FG content but readily digestible CP and AA in CDCP (unpublished data), and high levels of small peptides in P50 (Myers et al, ). Furthermore, all the diets in our study had similar DE and SID of lysine, methionine, threonine, and tryptophan, which explain the reason for no differences among dietary treatments.…”
Section: Discussionmentioning
confidence: 96%
“…In our study, AID of CP in S50 and HP300 diets was greater than that in P50 diets, which was inconsistent with our expected results. P50 as a dried porcine soluble containing lots of peptides should own high protein digestibility in small intestine due to greater utilization of peptides than intact proteins and free amino acids (Myers et al, ). However, Mateos, Mohiti‐Asli, Borda, Mirzaie, and Frikha () reported that P50 as a popular DPS was produced by spraying the porcine mucosa hydrolysate into SBM carriers, which might contribute to low protein digestibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the USA, the Swine Health Protection Act (1980) regulates feeding of 'garbage' (defined as waste derived from meat or other animal materials) to pigs, which is legal only after heating the materials to 212 • F for 30 min, and under license. However, processed products of animal origin are legal and valuable components of swine diets, notably rendered products, spray dried porcine plasma (SDPP), hydrolyzed proteins that are byproducts of heparin extraction, and pet food byproducts (Cromwell, 2006;Jablonski, et al, 2006;Peace, et al, 2011;Myers, et al, 2014). The Animal Feed Safety System (AFSS) of the Food and Drug Administration (FDA) approves feed additives; oversees regulatory compliance pertaining to feed manufacturing, labeling, storage, and distribution; and acts to remove unsafe feed from the marketplace.…”
Section: The Baby and The Bathwater: Feeding Products Of Swine Originmentioning
confidence: 99%